#### Answer

False.
6x +2 = 3 is the correct equivalent equation.

#### Work Step by Step

$x+\frac{1}{3}=\frac{1}{2}$
To get rid of the fraction multiply the entire equation by the lowest common multiple (LCM) of the denominators of the fractions. In this case, the denominator is 6. So multiply the entire equation by 6, which is done by multiplying all the terms by 6.
$x\times 6+\frac{1}{3}\times 6=\frac{1}{2}\times 6$
Simplifying the equation:
6x+2=3
As 6x+2=3 $\ne$ x+2+3, the statement is false.